Considerations on rapid sequence intubation as an alternative to the airway approach in patients with COVID-19 - José Julio Ojeda González (Medisur, 2020)
COVID-19 is a condition that may evolve towards severity and the patient may presents acute respiratory failure, acute respiratory distress syndrome secondary to the pneumonic process triggered by this condition, in the course of which an anesthetic-surgical procedure may be required, and , as a consequence of the conditions described above, a rapid sequence intubation.This work is aimed at offering a group of valid considerations in the new context, related to the appearance of COVID-19, providing details on the management of these patients´ airway. The steps to follow for performing rapid sequence intubation are detailed, considering the drugs to be used and the biosecurity measures to be taken into account, as well as the recommendations for subsequent management of the anesthetic-surgical procedure in patients with COVID-19.